Use of Construction Project Scheduling Methods in the Czech Republic - Jana, Nováková; Martin, Nový (IOP conference series. Materials Science and Engineering, 2021)
This article deals with research in the field of construction project scheduling in the Czech Republic. The aim of the research was to determine the scheduling maturity within project management in selected medium-sized and large companies and the change in the use of these methods during the global COVID-19 virus pandemic. The research presented in this article consists of three consecutive steps: determining the research area and the research question, designing a research plan, conducting data collection and analysis and compiling research results. For the purposes of this research, the research question was defined as follows: How do the project management scheduling methods differ depending on the company size in the selected companies in the Czech Republic? For understanding both the context and the situation in the surveyed companies, qualitative approaches to data collection and analysis were used, particularly in-depth interviews and encoding method. This approach was chosen mainly due to the fact that in case of quantitative research, the results tend to be improved by the respondents or irrelevant respondents are questioned. The semi-structured interview questions which were created based on the findings of the current state of scientific knowledge and literary research were used for the needs of in-depth interviews. Open questions (topics) related to the respondents' experience, perceptions and opinions were created as a part of the preparation process. The aim was to get more reliable and relevant answers to the questions asked. The research, which lasted for 6 months, involved 10 medium-sized and large companies from the Czech Republic. The change in the use of scheduling methods took place mainly in medium-sized companies. Large companies emphasized scheduling even before the pandemic, medium-sized companies often neglected this area - planning was not documented, linked to other projects, suppliers or customers. The pandemic has changed this situation. Companies that participated in this research have started to understand integrated scheduling approaches and are going to invest or consider to invest in complex software solutions in the near future.